2008
DOI: 10.1063/1.3040717
|View full text |Cite
|
Sign up to set email alerts
|

X-ray diffraction study of gold nitride films: Observation of a solid solution phase

Abstract: The structure of nitride containing gold films produced by reactive ion sputtering and nitrogen plasma etching is investigated using x-ray photoelectron spectroscopy and x-ray diffraction. It is found that gold nitride is a solid solution of nitrogen atoms dissolved in a fcc gold matrix. Differences between the strain and lattice parameters of gold and gold nitride films were observed and are explained by interstitial nitrogen present in the latter. c 2008 American Institute of Physics. [DOI: 10.1063/1.3040717… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 16 publications
0
7
0
2
Order By: Relevance
“…Further studies demonstrated that this component was also unstable under prolonged exposure to Xray radiation indicating the relative lack of stability of the nitrogen state associated with this peak [10]. In these initial studies it was believed, based upon the theoretical investigation of stochiometric gold nitride compounds [9], that the nitride was most likely in the form of a novel triclinic phase of composition Au 3 N. Subsequent synchrotron-based high resolution X-ray scattering studies [11] showed no evidence of a separate gold nitride phase, but did show an isotropic lattice expansion consistent with the incorporation of nitrogen in interstitial locations of the face-centred-cubic gold lattice.…”
Section: Review Of Current Methods For Production and Characterisatiomentioning
confidence: 95%
See 2 more Smart Citations
“…Further studies demonstrated that this component was also unstable under prolonged exposure to Xray radiation indicating the relative lack of stability of the nitrogen state associated with this peak [10]. In these initial studies it was believed, based upon the theoretical investigation of stochiometric gold nitride compounds [9], that the nitride was most likely in the form of a novel triclinic phase of composition Au 3 N. Subsequent synchrotron-based high resolution X-ray scattering studies [11] showed no evidence of a separate gold nitride phase, but did show an isotropic lattice expansion consistent with the incorporation of nitrogen in interstitial locations of the face-centred-cubic gold lattice.…”
Section: Review Of Current Methods For Production and Characterisatiomentioning
confidence: 95%
“…There are a number of different techniques by which gold nitride films can be produced such as ion implantation [8,9], reactive ion sputtering (RIS) [6,10,11], plasma etching [6,[12][13][14], reactive pulsed laser deposition [7] and plasma assisted physical vapor deposition (PAPVD) using pulsed arc discharge [15,16]. Moreover, gold nitride species have been found to exist in the gas phase: Drenck et al [17] observed the formation of nitrogen-gold AuN n -anions and dianions.…”
Section: Review Of Current Methods For Production and Characterisatiomentioning
confidence: 99%
See 1 more Smart Citation
“…When the samples M2 and M11 are compared with target, widening and small asymmetry in the (111) diffraction peak are observed. These features can be a consequence of the compressive or tensile stress in the thin films, because of, either a new phase (it is related to the interstitial nitrogen in the Au‐fcc structure), or the differences in thickness; nonetheless, the thickness was approximately equal (~420 nm, Table ). A preferential orientation in the (111) direction was observed in all samples, and small peaks were assigned to steel substrates.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, gold nitride species have been found in the gas phase: Drenck et al 6 observed the formation of nitrogen-gold AuN n − anions and dianions. In addition to the irradiation of single crystal samples with nitrogen ions in UHV, 2,4 gold nitride films have been formed by reactive ion sputtering, 5,7 by radio frequency plasma etching ͑rf-etching͒ 5,7,8 by reactive pulsed laser deposition, 9 and plasma assisted physical vapor deposition using pulsed arc discharge. 10 Work by Šiller et al 5 has shown that gold films with gold nitride display promising properties: they are harder than gold coatings while retaining a high electrical conductivity.…”
Section: Introductionmentioning
confidence: 99%